SISTEM INFORMASI MANAJEMEN SKRIPSI BERBASIS WEB DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Tri Pratiwi Handayani; Rubiyanto Maku; Rahmawati Musa (Jurnal Ilmu Komputer (JUIK), 2021)
This study aims to integrate all administrative processes in managing theses in a Web-based system and speed up the process of disseminating information or announcements, determining, determining exam schedules for students, evaluating student exam results and providing a means for online thesis guidance processes between lecturers and students. through a computerized chat feature via the website. This research uses the System Development Life Cycle (SDLC) system development model. This research resulted in a website-based system using the PHP programming language and using the MySql database. The results of this study broadly consist of three stages, namely the input stage which includes input of student registration data, lecturer data, schedule data, information/news data, value data, and determination data. determination of lecturers, scheduling process, examination assessment process, information dissemination process, and chat and correction processes while the output stage consists of the output of student test scores, determination of assistant lecturers, schedule and information.